Quantile regression analysis of the socioeconomic inequalities in air pollution and birth weight. (September 2020) - Lamichhane, Dirga Kumar; Lee, So-Yeon; Ahn, Kangmo; Kim, Kyung Won; Shin, Youn Ho; Suh, Dong In; Hong, Soo-Jong; Kim, Hwan-Cheol
Highlights: The associations of air pollution with birth weight distribution were examined. Associations between air pollution and reduced birth weight were of greater magnitude at the lower quantiles of birth weight. A pattern of greater negative association was found in the lower socioeconomic group. Abstract: Background: An association between maternal exposure to air pollution and the birth weight distribution has been reported, but the extent to which this relationship varies according to socioeconomic status (SES) is unknown. This study examined the relationship using the data from a Korean birth cohort. Methods: Data for singleton births in Seoul from 2007 to 2017 (n = 1739) were analyzed. Maternal exposures to particulate matter with an aerodynamic diameter <10 µm (PM10 ) and <2.5 µm (PM2.5 ), as well as to nitrogen dioxide (NO2 ) and ozone (O3 ) for each trimester and the entire pregnancy were estimated using residential address, gestational age, and the birth date. The associations between the interquartile range (IQR) increases in pollutant concentrations and the changes in birth weight were examined using linear regression and quantile regression models. The socioeconomic disparities in the associations were investigated using a derived SES variable based on the composite of parental education and occupation. This SES variable was then interacted with the air pollutant. Results: In the gestational age-adjusted models, particulate air pollutants (PM10 and PM2.5 ) and O3 were associated with birth weight decreases for the lower birth weight percentiles. For example, the decrease in mean birthweight per IQR increase in PM2.5 during second trimester was −21.1 g (95% confidence interval (CI) = −41.8, −0.4), whereas the quantile-specific associations were: 10th percentile −27.0 g (95% CI = −46.6, −7.3); 50th percentile −22.2 g (95% CI = −39.6, −4.8); and 90th percentile −22.9 g (95% CI = −45.5, −0.2). Particulate air pollutants and O3 showed a pattern of socioeconomic inequalities; the reduced birth weight was of greater magnitude for children from a low SES group. Conclusions: Negative associations between particulate air pollutants and O3 and birth weight were consistently greater at the lower quantiles of the birth weight distribution, especially in lower SES group.